Chinese fintech companies and their "going out" strategies. Issue 1 (24th September 2021) - Han, Alice Siqi
Abstract : Purpose: This paper outlines the rapid rise of China's fintech companies over the past decade with a focus on their globalization strategies as they enter their next phase of development. Design/methodology/approach: The author examines China's current and prospective influence on global financial digitization trends, and assesses both domestic and foreign opportunities and challenges confronted by China's fintech firms as they look to expand abroad. Findings: The Chinese government is experimenting with a radically new fintech system and a regulatory regime in response to it. Chinese ambitions to expand fintech influence through private companies and the state-led "digital RMB" (e-CNY) will likely provoke a wave of "digital protectionism" among developed nations to protect internal digital payments. Originality/value: This paper is an original economic history research on China's fintech industry.